Validation of a preoperative assessment scale in older adults to predict postoperative morbidity and mortality - Diaz-Velez, Cristian (2026)
Introduction: Preoperative risk stratification in older adults is a key component for reducing postoperative morbidity and mortality, given the high prevalence of comorbidities, frailty, and functional impairment in this population. However, commonly used risk assessment tools show limited predictive performance when applied to geriatric patients. Objective: To validate a preoperative assessment scale for predicting postoperative morbidity and mortality in older adults undergoing surgical procedures. Material and Methods: An analytical case-control study nested within a cohort of patients aged 65 years and older undergoing surgery was conducted. The scale was developed using clinical, functional, and laboratory variables selected through logistic regression analysis. Predictive performance was assessed using receiver operating characteristic (ROC) curves, along with sensitivity, specificity, and predictive values. Model stability was evaluated through internal validation in an independent cohort. Results: The scale demonstrated high specificity and moderate overall discriminative ability for predicting adverse postoperative outcomes, although sensitivity was low. The area under the ROC curve indicated acceptable performance for identifying patients at low postoperative risk. Internal validation confirmed the stability of the model coefficients and overall predictive behavior. Conclusions: The validated scale may assist in identifying older adults at low risk of postoperative morbidity and mortality and could serve as a complementary tool in preoperative assessment. However, its low sensitivity limits its use as a screening instrument.